2022
DOI: 10.3390/ijerph191711089
|View full text |Cite
|
Sign up to set email alerts
|

Public Health Services, Health Human Capital, and Relative Poverty of Rural Families

Abstract: With the successful completion of the battle against poverty, after 2020, the focus and difficulty of China’s poverty governance will change from solving absolute poverty to alleviating relative poverty. Analyzing and studying the alleviation of relative poverty from the perspective of public health services is in line with the current needs of consolidating and expanding poverty alleviation in China, and it is also of great significance to building a long-term solution mechanism for relative poverty. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 28 publications
0
11
0
1
Order By: Relevance
“…This conclusion serves as a crucial validation and supplement to the research of Yang et al (2022), Michael et al (2020), and Xavier et al (2001). Yang et al (2022) found that the accumulation of health human capital and enhancing individual agency can effectively alleviate poverty [ 80 ]. Michael et al (2020) recognized the pivotal role of entrepreneurship in addressing poverty issues [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This conclusion serves as a crucial validation and supplement to the research of Yang et al (2022), Michael et al (2020), and Xavier et al (2001). Yang et al (2022) found that the accumulation of health human capital and enhancing individual agency can effectively alleviate poverty [ 80 ]. Michael et al (2020) recognized the pivotal role of entrepreneurship in addressing poverty issues [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sen explains poverty in terms of “Viable Capabilities”, arguing that good health is a condition for individuals to develop other likely and viable capabilities [ 79 ]. Improved health also alleviates health-related poverty, and facilitates the satisfaction of other needs [ 80 ]. Phoumin et al (2019) analyzed data from the 2015 Cambodia Socio-Economic Survey (CSES) and found a negative relationship between multidimensional energy poverty and household health in Cambodia [ 81 ].…”
Section: Theoretical Background and Research Hypothesismentioning
confidence: 99%
“…Una buena salud es esencial para el desarrollo y el rendimiento de las personas, ya su vez, el capital humano puede influir en la salud a través del acceso a mejores empleos, condiciones laborales y estilos de vida saludable (Amar et al, 2022;C. Victora et al, 2022;Xu et al, 2023;Yang et al, 2022).…”
Section: Discussionunclassified
“…Among them, educational level, health condition and number of workforce members in the family are important human capital elements. Being a village cadre or not determines whether the farmers can obtain more social resources [67][68][69][70]. The variables of resource endowment include the farmland area of households and the forest area of households.…”
Section: Variable Selectionmentioning
confidence: 99%